Biodegradable versus durable polymer drug eluting stents in coronary artery disease: Insights from a meta-analysis of 5834 patients. (29th August 2020) - Lupi, Alessandro; Rognoni, Andrea; Secco, Gioel Gabrio; Lazzero, Maurizio; Nardi, Federico; Fattori, Rossella; Bongo, Angelo Sante; Agostoni, Pierfrancesco; Sheiban, Imad
Abstract: Background: Biodegradable polymer drug eluting stents (BP-DES) have been developed to overcome the limitations of first generation durable polymer DES (DP-DES) but the clinical results of different BP-DES are not consistent. We performed a meta-analysis to compare the outcomes of BP-DES and DP-DES in the treatment of coronary artery disease (CAD). Methods and results: Online databases including MEDLINE were searched for studies comparing BP-DES and DP-DES for obstructive CAD that reported rates for overall mortality, myocardial infarction (MI), late stent thrombosis (LST), target lesion revascularization (TLR) and late lumen loss (LLL) with a follow-up of ≥6 months. Ten studies (5834 patients) with a 1-year median follow-up were included in the meta-analysis. When comparing patients treated with DP-DES and BP-DES those treated with BP-DES had lower LLL (in-stent: weighted mean difference (WMD) −0.10 mm, 95% CI = −0.17 to −0.03 mm, p  = 0.004; in-segment: WMD −0.06 mm, 95% CI = −0.10 to −0.01 mm, p  = 0.01) with lower TLR rates (OR 0.67, 95% CI = 0.47 to 0.98, p  = 0.04). However, BP-DES did not improve mortality (OR 0.97, 95% CI = 0.73 to 1.29, p  = 0.83), MI (OR 1.13, 95% CI = 0.87 to 1.46, p  = 0.36) or LST rates (OR 0.64, 95% CI = 0.36 to 1.16, p  = 0.14). A pre-specified subgroup analysis of Biolimus BP-DES confirmed significant LLL reduction without differences in other clinical endpoints. Meta-regression analysis demonstrated a strong significant inverse correlation between LLL and reference coronary diameter ( p  < 0.001). Conclusions: Our present meta-analysis showed that BP-DES when compared with DP-DES significantly reduced LLL and TVR but without clear benefits on mortality, MI and LST rates. (Clinicaltrials.gov identifier: NCT01466634).